Responsible business: Analyzing the impact of corporate ESG on employee pay inequality - Pengfei Zhou; Shuwan An; Yang Shen (Sustainable Futures)
Against the backdrop of increasing emphasis on corporate social responsibility and sustainable development, this study utilizes data from China's A - share listed companies over the period of 2009 to 2022 to empirically examine the influence of Environmental, Social, and Governance (ESG) performance on the internal pay gap. The research is significant as it sheds light on how ESG practices, which are gaining importance in the corporate world, affect income distribution within companies. The scope of the study covers a wide range of firms in China, providing comprehensive insights into this relationship. The benchmark regression results indicate a significant positive correlation between ESG performance and the internal pay gap, a finding that remains robust through various tests. The mechanism analysis reveals that ESG performance affects the internal pay gap by influencing business performance, principal - agent costs, and labor reallocation. Moreover, the heterogeneity analysis shows that ESG performance has a more pronounced impact on the internal pay gap of high - market - value companies, non - high - tech firms, and capital - intensive enterprises. These findings have important implications for corporate management and policy - making. To optimize the human capital structure and improve the internal income distribution mechanism, it is recommended that companies enhance their ESG practices, pay attention to the specific characteristics of different types of enterprises, and take measures to address the potential widening of the pay gap while promoting sustainable development.